Understanding urban rail in-vehicle activities: An activity theory approach. (April 2017) - Camacho, Tiago; Foth, Marcus; Rakotonirainy, Andry; Rittenbruch, Markus
Highlights: Qualitative study of urban rail in-vehicle activities. Activity theory was applied as a theoretical lens. Approach was useful in providing a more in-depth understanding of in-vehicle activities and their impact on how the service is experienced by passengers. Designing in-vehicle activities that cater to the underlying needs of passengers has the potential to elicit better overall service responses. Abstract: Public transport in-vehicle activities are activities undertaken by passengers while en-route to their destination. Recent focus has been given to this subject, as evidence accrues to demonstrate the influence that in-vehicle activities have on the way passengers perceive and assess the service as a whole. Still, most of research regarding public transport in-vehicle activities has been descriptive in nature—i.e., activities are identified and described, but a further consistent depiction of what defines, shapes, and restricts in-vehicle activities in the context of public transport is lacking. This gap makes it difficult to study public transport in-vehicle activities from an established perspective, resulting in scattered knowledge about activities, underlying motives, and the impact that activities can have on passengers. This research makes uses of a novel approach to the study of urban rail in-vehicle activities using activity theory. Through the use of a qualitative approach, we put forward a model that allows for the systematic structuring of in-vehicle activities and the identification of the elements that define and influence such activities. Additionally, in this research we explore how in-vehicle activities are undertaken by passengers and how they impact their subjective perception of the journey. Our results show that our approach is useful in gaining both a high level understanding of urban rail in-vehicle activities, as well as enabling to identify and analyse the individual factors that can impact these activities. We see this study as a step forward in shaping urban rail as a method of transport that promotes activity undertaking so as to better align with passengers' subjective and dynamic needs.